Application Of Liquid Chromatography With Tandem Mass Spectrometric Method For Quantification Of Safinamide In Invitro Samples: Pharmaceutical Science-Pharmaceutical analysis for Novel drug formulation - Mohan Rao Tammisetty; Balasekhara Reddy Challa; Srinivasa Babu Puttagunta (International Journal of Life Science and Pharma Research, 2022)
Safinamide is a novel drug with both dopaminergic and non-dopaminergic effects, approved first by the European Commission and more recently by the US Food and Drug Administration (FDA) as an adjunctive treatment to carbidopa/levodopa in patients with mid- to late-stage Parkinson’s disease (PD) and motor fluctuations. The validated analytical method was applied for the estimation of Safinamide in aqueous solution and human plasma with Safinamide-D4 as an internal standard by using UPLC-MS/MS. The chromatographic separation was achieved with 0.1% formic acid solution: Methanol, 30:70% v/v using CORTECS C18 with 100 x 4.6, 2.7 µ. The total analysis time was 4 min, and the flow rate set to 0.8 mL/min. The mass transitions of Safinamide and Safinamide-D4 obtained were m/z 303.3 and 215.2 and 307.3 and 215.2. The standard curve shows a correlation coefficient (r2) greater than 0.998 with a range of 113.0-338.0 pg/mL using the linear regression model. The method has shown good reproducibility, as intra- and interday precisions were within 10% and accuracies were within 8% of nominal values for both analytes. The method was successfully applied for the forced degradation studies at various stress conditions.